The role of dendritic spines in epileptogenesis - Jean, Gary; Carton, Joseph; Haq, Kaleem; Musto, Alberto E. (Frontiers in Cellular Neuroscience, 2023)
Epilepsy is a chronic central nervous system (CNS) disease associated with high morbidity. To date, there is no known disease-modifying therapy for epilepsy. A leading hypothesis for a mechanism of epileptogenesis is the generation of aberrant neuronal networks. Although the underlying biological mechanism is not clear, scientific evidence indicates that it is associated with a hyperexcitable synchronous neuronal network and active dendritic spine plasticity. Changes in dendritic spine morphology are related to altered expression of synaptic cytoskeletal proteins, inflammatory molecules, neurotrophic factors, and extracellular matrix signaling. However, it remains to be determined if these aberrant dendritic spine formations lead to neuronal hyperexcitability and abnormal synaptic connections or whether they constitute an underlying mechanism of seizure susceptibility. Focusing on dendritic spine machinery as a potential target for medications could limit or reverse the development of epilepsy.